Sustainable Tourism: Analysis of the AISAS Model Through Instagram Social Media @TRAVELXISM During Voluntrip Activities - Salsabila, Elvira; Jailani, Muhammad; Ali, Muhammad (Journal of Social and Policy Issues, 2025)
Instagram account @Travelxism focuses on travel and exploration of tourist destinations, aims to integrate a social media management approach that focuses on sustainable tourism through Voluntrip activity content, this Instagram account aims to make its followers more aware of sustainable tourism and encourage actions that support the principles of sustainable tourism The purpose of this study is to analyze the extent to which the use of the Travelxism Instagram account in Voluntrip Activities and the strategies used in developing sustainable tourism This research is qualitative using secondary data through a review of the literature review of the general description of marketing communication strategies through the Instagram account "TRAVELXISM" By using the AISAS theory model analysis, an effective approach can be taken to the target audience by considering behavioral changes that occur on various digital platforms, such as social media using the VOSViewer tool to view and map several themes in this data analysis and also using NVivo 12 plus, which maps the problems studied by previous studies based on the overall manuscript problem The conclusion that is the reference of researchers to the theory put forward by Heillbronn, namely environmentally sustainable, economically sustainable, and socio-culturally sustainable, it can be concluded that the @travelxism account carries out digital activism through Voluntrip activities by taking several strategic steps. The first step is to build a social media account that focuses on eco-friendly travel. The second step is to implement the concept of sustainability through news and visual actions, as well as introducing culture, local crafts, and art exhibitions. The third step is to optimize actions that are seen as the right actions.